The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.2215/cjn.02400706
|View full text |Cite
|
Sign up to set email alerts
|

Proteinuria-Lowering Effect of Heparin Therapy in Diabetic Nephropathy without Affecting the Renin-Angiotensin-Aldosterone System

Abstract: Angiotensin-converting enzyme inhibitors and angiotensin II (AngII) type 1 receptor blockers lower proteinuria and preserve renal function in diabetic nephropathy (DN). The antiproteinuric effects are greater than their blood pressure reduction, involving the sieving properties of the glomerular filter. In DN, glomerular staining for heparan sulfate proteoglycans is decreased. AngII inhibits heparan sulfate synthesis. Also, heparins modulate AngII signaling in glomerular cells, inhibiting aldosterone synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…23,24) On the other hand, heparin therapy is known to have a proteinuria-lowering effect, which cannot be explained via the RAA system. 25) van der Pijl et al reported that danaparoid, which is a mixture of sulfated glycosaminoglycans, significantly lowered proteinuria in type 1 diabetic nephropathy. 26) They suggested that danaparoid supplements the action of proteoglycans, rather than inhibiting factor Xa.…”
Section: Discussionmentioning
confidence: 99%
“…23,24) On the other hand, heparin therapy is known to have a proteinuria-lowering effect, which cannot be explained via the RAA system. 25) van der Pijl et al reported that danaparoid, which is a mixture of sulfated glycosaminoglycans, significantly lowered proteinuria in type 1 diabetic nephropathy. 26) They suggested that danaparoid supplements the action of proteoglycans, rather than inhibiting factor Xa.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of enoxaparin, which is a low‐molecular‐weight heparin, in patients with diabetic nephropathy exerted antiproteinuric effect not via the renin‐angiotensin‐aldosterone system, but apparently by inducing intrinsic alterations in the glomerular filter (Benck et al. , 2006).…”
Section: The ‘Sweet’ and ‘Bitter’ Effect Of Gag In The Pathophysiologmentioning
confidence: 99%
“…Enoxaparin, a low-molecular weight heparin, was also tested on patients with diabetic and non-diabetic glomerulopathies. The proteinuria-decreasing effect of this heparin was found not to be related to the renin-angiotensin system, and its glomerular filter-related effect was suggested [45]. …”
Section: Experimental Data Supporting the Potential Use Of Glycosaminmentioning
confidence: 99%
“…Angiotensin II inhibits HSPG expression in human podocytes [47] and heparins modulate AT-II signalling in glomerular cells [48], inhibiting aldosterone synthesis [49] and lowering proteinuria in diabetic patients [45], but this effect is less pronounced in other forms of proteinuric renal diseases and its relation to haemodynamic changes produced by RAS is not proven in clinical trials [45]. Of course, heparins are not easily administrable for chronic treatments.…”
Section: Experimental Data Supporting the Potential Use Of Glycosaminmentioning
confidence: 99%